Assessing the Tax Liability Using an Option-Based Model - Vlachý, Jan, 1964-; Hnilica, Jiří, 1976-; Pošta, Vít, 1980-; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2009)
This Thesis uses several forms of a single-period option-based model to analyze the incidence of income tax under uncertainty, focusing on the various effects of tax asymmetries and observing the distinct features of individual and corporate taxation. Two particular applications are being advanced. The one strives to establish the economic effects of tax-deductibility, motivated initially by a thin-capitalization measure brought forth under the framework of the recent Czech public-finance reform. The pother one compares the terms of three distinct personal income-tax schedules, as they have been recently applied in the Czech Republic and Slovakia, investigating particular issues such as tiered rates, mandatory minimum tax, bracket creep, social taxes, as well as tax incidence in general. On the whole, we find that option-based models are well suited for miscellaneous forms of economic analysis under dynamic assumptions, overcoming the inherent limitations of comparative statics routinely used by mainstream economics. We also conclude that the Czech tax reform of 2008 has failed to achieve the level of economic neutrality and simplicity, characteristical for the Slovak flat-tax schedule of 2004. There are cases, where it has actually contributed to the emergence of new asymmetries.
Vedoucí práce: Jiří Hnilica
Disertační práce (Ph.D.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2009
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2009
Způsob přístupu: Internet
Keywords: podniková ekonomika a management [obor disert. práce]; disertace; dissertations